The distribution of path loss exponent in 3D indoor environment - Mohamad Razali, Nur Atina; Habaebi, Mohamed Hadi; Zulkurnain, Nurul Fariza; Islam, Md. Rafiqul; Zyoud, Al-Hareth (Research India Publications, 2017)
Wireless communications in indoor environment such as wireless sensor network and WiFi is slowing becoming the norm of everyday business, especially in industrial indoor settings. Tracking flying objects in an indoor environment controlled via wireless links require proper understanding of the path loss distribution in a 3D environment. Such a setting is rarely discussed - if any - in the open literature where the path loss exponent is generalized over the whole 3D indoor space. This study, however, attempts to address minute changes in path loss exponent distribution in such environment. An extensive measurement campaign was conducted in our university laboratory mimicking an industrial indoor setting where drones are supposed to operate. Our initial study involved a placement of 2.4 GHz transmitter at different heights with 0.00 m, 0.61 m, 1.36m and 1.88 m while varying the receiver antenna location over a 3D grid of 1 meter resolution in x, y, and z-axes directions. The received signal strength indicator (RSSI) readings were recorded to derive the path loss exponent at every grid point. Interestingly, results indicate that path loss exponent is definitely affecting along the z-axis (vertically) but still can be averaged over x-y- axes (horizontally). Increasing the transmitter or receiver height decreases the path loss exponent averaged over the s-x axes grid lines. Furthermore, due to furniture clutter on the floor and the availability of clear LOS components at higher links, the path loss becomes a function of the height. The results confirm further the furniture clutter and the floor proximity do add up to the path loss exponent due to lack of LOS links while higher links experience smaller path loss exponent. This is quite important as it has never been reported in the open literature before.